2023
DOI: 10.1039/d3gc01500a
|View full text |Cite
|
Sign up to set email alerts
|

Facile design of renewable lignin copolymers by photoinitiated RAFT polymerization as Pickering emulsion stabilizers

Abstract: As the richest aromatic renewable resource, lignin has attracted significant attention for fabricating various materials. However, due to lignin’s structural complexity, an effective and facile structural modification strategy remains a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…Meanwhile, RAFT polymerization is characterized by mild reaction conditions, the absence of metal catalysts, and versatility in the choice of monomers. , Li et al fabricated a light-responsive bifunctional fluorinated polyacrylate through RAFT-aided Pickering emulsion polymerization with self-healing ability. Liu et al synthesized the lignin graft copolymers DL-P­(MMA-AA) and DL-P­(MMA-AM) using a photoinitiated RAFT method, which could self-assemble into spherical nanoparticles and form stable Pickering emulsions in aqueous environment. Cyclodextrins (CDs) were known as “green” molecular hosts and had received widespread attention due to their low cost, easy accessibility, and biocompatibility .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, RAFT polymerization is characterized by mild reaction conditions, the absence of metal catalysts, and versatility in the choice of monomers. , Li et al fabricated a light-responsive bifunctional fluorinated polyacrylate through RAFT-aided Pickering emulsion polymerization with self-healing ability. Liu et al synthesized the lignin graft copolymers DL-P­(MMA-AA) and DL-P­(MMA-AM) using a photoinitiated RAFT method, which could self-assemble into spherical nanoparticles and form stable Pickering emulsions in aqueous environment. Cyclodextrins (CDs) were known as “green” molecular hosts and had received widespread attention due to their low cost, easy accessibility, and biocompatibility .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, researchers have begun to synthesise bio-based waterborne polyurethanes (WPUs) using water as the dispersion medium and bio-based materials instead of petroleum-based materials. 10–13 Carboxylic acid-containing chain extenders, which introduce carboxyl groups to make the molecular chain hydrophilic, are frequently used in waterborne polyurethanes to improve dispersion in the aqueous phase. Further, polymers containing carboxyl groups can adhere to enamel and dentin surfaces by forming ionic bonds with calcium from hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, lignin, the second most abundant component in plants, is rich in phenolic hydroxyl groups and phenyl rings, and it is used widely in various fields, such as adhesives, optical switching, nanomaterials, and hydrogels. , Despite significant progress, the heterogeneity and low reactivity of lignin severely limit its applications. Previously, chemical modification, functionalization, or nanotechnology enhanced lignin’s reactivity and performance. For example, Lu et al reported a hydrogel prepared using silver-lignin nanoparticles, which exhibits excellent self-healing capability and long-term stable adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…7,22 Despite significant progress, the heterogeneity and low reactivity of lignin severely limit its applications. Previously, chemical modification, 23 functionalization, 24 or nanotechnology 22 ance. For example, Lu et al 22 reported a hydrogel prepared using silver-lignin nanoparticles, which exhibits excellent selfhealing capability and long-term stable adhesion.…”
Section: ■ Introductionmentioning
confidence: 99%